Through moments in history : memoirs of two decades of intellectual and social life, 1970-1990 - Rahman, Md. Anisur (Muhammad Anisur) (Pathak Shamabesh, 2007)
Memoirs of an economics professor and official of the International Labour Office (Geneva) from Bangladesh.